Potential Colon Cancer Biomarker Search using more than two Performance Measures in a Multiple Criteria Optimization Approach - Watts-Oquendo, Érika; Sánchez-Peña, Matilde; Isaza, Clara E.; Cabrera-Rios, Mauricio (Puerto Rico Health Sciences Journal, 2012)
Objective: A new method using Multiple Criteria Optimization (MCO) proposed by our research group has shown evidence of being able to identify gene-based biomarkers for the detection of cancer using microarray data. Herein, we explore this method, considering more than two conflicting criteria for the MCO problem. Using this method would result in stronger outcomes when using different results from microarray analyses. It would also demonstrate that the method is suitable for carrying out meta-analysis. Methods: Statistical comparisons between normal and cancer tissues were performed using a colon cancer microarray database. The different comparisons were carried out with a Mann–Whitney non-parametric test using partial permutations of the data. An MCO problem was built using the different p-values obtained. The associated solution was the set of genes reaching the best compromises between the p-values under consideration that were located in the so-called efficient frontier. Data Envelopment Analysis (DEA) was used to find the efficient frontier of the MCO problem. The capacity of DEA was explored using different numbers of p-values (criteria) in the model. Results: The set of identified genes was consistent across the instances using different numbers of p-values in the DEA model, thereby providing evidence of the outcome stability of the proposed strategy. It was also observed that convergence to a larger number of potential biomarkers is faster with additional criteria, i.e., more p-values. Conclusion: The MCO problem proposed for the cancer biomarker search using microarray data can be solved efficiently with DEA using more than two conflicting criteria. This approach can result in robust results when using different analyses of microarray data and, indeed, in a faster convergence to highly potential biomarkers.